Prevalence of glucose intolerance and factors that influence it among pregnant women with and without risk at Antenatal Clinic, HUKM. Cheras, 1999 - Siti Rafiaah Ismail,; Khadijah Shamsuddin, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross- sectional study on glucose intolerance and gestational diabetes using 2-HPP blood sugar was conducted al!1Jng pregnant women without risk factors and with risk factors like age maternal age more than 35 years, maternal weight more than 80 kg, positive family history of diabetes mellitus, previous obstetric history of gestational diabetes, give birth to baby with congenital malformation, stillbirth, neonatal death, polihydrarnnios, spontaneous abortion, give birth to baby more than 4 kg, vaginal discharge, urinary tract infection, glycosuria, and abnormal random blood sugar. The purpose of this study is to measure the prevalence of glucose intolerance and gestational diabetes and assess the association between selected screening factors with abnormal 2-HPP blood sugar. This cross-sectional survey involved 660 pregnant women attending the antenatal clinics in Hospital UKM between 1st June 1999 until 30th December 1999 using universal sampling. Most of the mothers are Malays (59.2 %), between the ages of 19-34 (85.5 %), with secondary and high education (93.8 %), working (60.6 %) and primiparous (57.9 %). Results show 162 antenatal mothers (24.5%) had abnormal glucose tolerance based on 2-HPP blood sugar of 7.8 mmol/1 and 17 (2.6 % ) antenatal mothers had gestational diabetes with 2- HPP blood sugar of 11.1 mmol/l. The most c('"11monly identified screening factors in this population . was positive family history' 'of diabetes mellitus (30.8 % ), followed by vaginal discharge in current pregnancy (16.8%), and maternal age more than 35 years (14.6 %). With regards to overall screening factors 281 (42.6 %) of antenatal mothers had no risk factors, 379 (57.4 %) had at least one risk factor 130 (19.7 %) had 2 or more risk factors and 34 (5.2 %) had 3 or more risk factors. As a whole screening test which took pregnant women with 2 or more risk factors had good sensitivity and spesificity (74.7% and 82.1 %) towards glucose intolerance. Almost all risk factors had high spesificity but low sensitivity towards both glucose intolerance and gestational diabetes. However random blood sugar had high spesificity towards glucose intolerance and gestational diabetes (89.4 % and 87.7 % ) but it only sensitive to gestational diabetes (70.6 %). Measurement of yield showed overall yield of the risk factors increased with increase number of risk factors for glucose intolerance. The yield was between 15.8% to 58.3 % for glucose intolerance and between 0 to 16.7 % for gestational diabetes.